Play Ball: A 10-Year Comparative Analysis of Craniofacial Safety in Baseball and Softball. Issue 6 (29th September 2022) - Riccio, Charles A.; Balaji, Navin; Pierrot, Randall; Wolfe, Erin; Slavin, Benjamin R.; Kaplan, Nate; Kaplan, Lee; Thaller, Seth R.
Abstract : Introduction: Within the United States, the number of players participating in baseball increased by nearly 21% to 15.9 million between 2014 and 2019. Additionally, batting helmets with face-masks are encouraged yet optional in youth baseball as well as college baseball and softball. in light of inconsistencies in safety equipment enforcement and usage, this study aims to perform a comparative analysis of the number and frequency of baseball and softball-related craniofacial injuries (CFis). Methods: Data regarding baseball and softball-related injuries were gathered from the National Electronic Injury Surveillance System database from 2011 to 2020. Craniofacial injuries were isolated and organized into 5-year age groups beginning with 5 to 9 years and ending with 25 to 29 years of age. Data was further stratified by location and type of injury. Injury types specifically reported in this study included concussion, contusion, fracture, and laceration. Results: Distribution of injuries across age groups differed significantly between baseball and softball ( P < 0.001). When comparing the 10 to 14 year old group to the 15 to 19 year old group, we found that concussions and head contusions comprise a significantly greater proportion of all injuries in softball than in baseball. Conversely, facial fractures, facial lacerations, and mouth lacerations comprise a significantly greater proportion ofinjuries in baseball than in softball. Conclusion: Future prospective studies aiming to better characterize the within-game nature of these reported CFIs would certainly be beneficial in guiding the baseball and softball communities toward consideration of implementing maximally efficacious updates to current safety equipment standards.